Property rights and owner occupied housing investment in urban Ethiopia. Issue 4 (15th August 2016) - Hailu, Ziade; Rooks, Gerrit
Abstract : Purpose: The purpose of this paper is to investigate whether the provision of formal land and building rights provides incentives to poor households to invest in their property in urban Ethiopia. Design/methodology/approach: To test our hypothesis a natural quasi-experimental design was employed. Data was collected from a random sample of 210 households in a land formalization project and 190 households in a control group in Addis Ababa, Ethiopia. To control for selection bias propensity score matching was used to estimate group differences. Findings: The beneficiary group reported a higher investment level than did the control group. Households in the beneficiary group are statistically more likely to invest in new structures and housing maintenance, yet these effects are modest. Practical implications: Governments, donors, and land administration officials may use these findings to address contextual issues that need deliberate interventions to make formalization projects achieve its goals. Originality/value: Property rights research is preoccupied with changes in land rights and its response to investment in agricultural sector. The paper contributes to the limited literature dealing with property rights literature on urban setting. Moreover, empirical research has been hampered by the problem of causality and endogeneity while our study is designed in such a way to respond to the selection problem utilizing a natural experiment.